Is This My Country? Identification With National Symbols in Serbs and Bosniaks in B&H - Karić, Tijana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Although the war in B&H ended more than 20 years ago, ethnic tensions continue to be present. The aim of this article is to present the level and differences between Serbs and Bosniaks in identification with national symbols of B&H. The representative sample consisted of 1308 participants, 58.7% of Bosniak ethnicity, living in Bosnia & Herzegovina. The data is collected by IPSOS as a part of the project Strategies of symbolic nation-building in West Balkan states: intents and results. The results have shown that Bosniaks identify significantly more with all national symbols, including the flag, the anthem, the coat of arms, and the holidays. They also consider B&H to be their patria significantly more than the Serbs. Both groups estimate low level of quality of intergroup relationship. Bosniaks are more prone to express dual ethnic and national identity, while Serbs tend to identify themselves only with their ethnic group. The results are discussed in the light of social identity theory.